论张锦忠和李有成的离散论述: Malaysian Chinese Literature and Diaspora Studies: Tee Kim Tong and Lee Yucheng's Discourses - Poh, Goh Siew (ERUDITE: Journal of Chinese Studies and Education, 2021)
马华文学自1990年代以降开始进入离散研究的视野，不少学者发表若干论文讨论马华离散文学，其中以在台学者张锦忠、李有成的论述最为系统化和体系化，值得特别关注。马华文学的离散研究其实获益自海外华人研究、西方离散研究等领域，它有几个重要面向，首先离散研究着重跨国网络而非国家本位，如此的视角更契合当代资本主义全球化下频繁的跨国流动现象。其次，离散研究也借着“离散华人”（Chinese diaspora或diasporic Chinese）的概念来与中国人（Chinese）身份做区分，从而为在中国之外的中国人与其后裔寻找本土在地的定位。第三，作为经验性的研究术语或作为描述与分析的概念，也随着论述的进一步开展，渐渐地从历史的描述与分析工具发展成批判工具，并成为一套实践理论。马华文学固然在离散研究下获益良多，然而在离散研究发展至今已有二十余年，关于离散的定义、边界等仍众说纷纭、莫衷一是，我们有必要把“离散论述”重新问题化，检视其中可能存在的问题。本文认为离散研究在经历“一般化转向”后，已经从原本特殊语境的离散（犹太人、非洲人被迫离开家园的历史概念）转向一般化语境的离散（现代全球化下的普遍现象），这转向过程必然牵扯到重新界定该术语的重重难题，离散研究中诸多矛盾也与此有关。其次，离散研究不满足于仅仅描述历史现象，更尝试从离散中提炼出批判意识与方法，并进一步扩展成可提高公民素养的思想资源，然而其证立基础却相当可疑，有必要仔细检验。Mahua (Malaysian Chinese) Literature has been an academic field in diaspora studies since the 1990s. Lee Yucheng and Tee Kim Tong, both Malaysian-born, are among the scholars who have developed the theory thoroughly in Taiwan. The diaspora studies of Mahua Literature was benefited from Chinese diaspora studies and the Western diaspora studies, hence its outcome encompasses a few dimensions. Firstly, it focuses more on transnational network instead of national literature per se, in which such perspective is in line with the rise of globalization in modern capitalism. Secondly, the concept of Chinese diaspora (or diasporic Chinese) is used to distinguish the identity of the mainland Chinese. Thirdly, diaspora studies has shifted from empirical studies to critical studies, equipping scholars to reflect on more issues in Mahua Literature. Nevertheless, two decades after the establishment of the field, there are still questions needed to be asked and discussions worth revisiting. This article argues that after the “generalization turn”, the original discourse of the diaspora studies has shifted from the specific historical reference of the Jews and Africans, to a broader context which would include the diasporic experience of other ethnic groups such as Chinese, under the global transnational phenomenon which has become so common in today’s world. This transition has unavoidably brought new challenges, especially regarding the definition and the boundaries of the studies. While some scholars also attempt to further develop the concept of “diaspora” to become a critical theory instead of a mere historical idea, more valid foundation and reflections are still much needed.Keywords: Chinese diaspora, Mahua literature, Local, China, Lee Yucheng, Tee Kim Tong.